ITEM QUALITY ANALYSIS FOR MEASURING MATHEMATICAL PROBLEM-SOLVING SKILLS - Palupi Sri Wijayanti (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2020)
This research aims to determine the quality of the questions used to measure students ' mathematical problem-solving skills. This type of research includes quantitative descriptive research. The research subject is a grade VII student with a primary data source is scores of mathematical problem-solving skills. The research instrument used was a written test to measure problem-solving abilities. The data analysis technique used is a quantitative analysis by looking at the validity, reliability, differentiation power, and bullet-grain index of the matter. The results showed that the problem has been valid, the reality belongs to the category quite well, the differentiator power for three items, including bad, enough, and good classes. Meanwhile, the difficulty index shows a number in the easy category, and two names are included in the medium category. Thus, it concluded that the instruments used to measure problem-solving abilities are valid and in a suitable category. It can see it from the instrument trial results with the percentage value of students' problem-solving abilities, which is included in the very high category, namely 20%. The number of students who have problem-solving skills in great variety could be presented at 53.33%. Students who have sufficient and low problem-solving abilities were given at 16.67% and 10%.Penelitian ini bertujuan untuk mengetahui kualitas butir soal yang digunakan untuk mengukur kemampuan pemecahan masalah matematika siswa. Jenis penelitian ini termasuk penelitian deskriptif kuantitatif. Subjek penelitian adalah siswa kelas VII dengan sumber data utama adalah skor kemampuan pemecahan masalah matematika. Instrumen penelitian yang digunakan adalah tes tertulis untuk mengukur kemampuan pemecahan masalah. Teknik analisis data yang digunakan adalah analisis kuantitatif dengan melihat validitas, realibilitas, daya pembeda, dan indeks kesukaran butir soal. Hasil penelitian menunjukkan bahwa butir soal telah valid, realibilitas termasuk dalam kategori cukup baik, daya pembeda untuk tiga butir soal termasuk kategori buruk, cukup, dan baik. Sementara itu, indeks kesukaran soal menunjukkan satu nomor dalam kategori mudah dan dua nomor termasuk dalam kategori sedang. Dengan demikian, dapat disimpulkan bahwa instrumen yang digunakan untuk mengukur kemampuan pemecahan masalah telah valid dan berkategori baik. Hal ini terlihat dari hasil ujicoba instrumen dengan persentase nilai kemampuan pemecahan masalah siswa yang termasuk dalam kategori sangat tinggi yaitu 20%. Jumlah siswa yang memiliki kemampuan pemecahan masalah dengan kategori tinggi dapat dipresentasekan sebesar 53,33%. Siswa yang memiliki kemampuan pemecahan masalah dengan kategori cukup dan rendah dipresentasekan sebesar 16,67% dan 10%.